PENGARUH MENGONSUMSI BISKUIT MANIS DAN ASIN TERHADAP PERUBAHAN pH SALIVA PADA MAHASISWI DI ASRAMA KEPERAWATAN GIGI POLTEKKES PALEMBANG - Masayu Nurhayati; Saluna Deynilisa (Jurusan Keperawatan Gigi, Poltekkes Kemenkes Palembang, 2019)
Eating foods that contain excessive carbohydrates tends to increase tooth decay, one of which is eating foodsthat contain sugar in carbohydrates. The sugar in carbohydrates contained in these foods is a substrate andmedia for bacterial growth, which will increase the process of tooth decay due to a decrease in salivary pH dueto demineralization. This study aims to determine an effect of salivary pH before and after consuming sweet andsalty biskuits. This study was an experimental study with bivariate data analysis using Anoa test. The sampleused was 64 female students in the Palembang Nursing Dental Boarding School dormitory. The results of thisstudy were salivary pH before and after consuming 0.26% sweet biskuits and 0.38% salted biskuits. Sweet andsalty biskuits were both able to reduce salivary pH but a decrease in pH after consumption of sweet biskuits wasgreater than salty biskuits and was statistically significant.